High performance organization and organizational effectiveness in BAPPEDA (Development and Planning Board), Aceh-Indonesia - Yusmita, Fifi; Sanjeevkumar, Virmala (IJRCM, 2012)
The Purpose of this paper is to identify the factors that effect High Performance Organizations and examining the relationship between High Performance Organization and organizational effectiveness.Two hypotheses were build based on the literature and the model and were tested in perspective of the previous studies and literature.The study focuses on the practice and observance of the two central factors, High performance Organization which leads to organizational effectiveness.A total of 40 of usable questionnaire were distributes.The finding shows that the independent variable was an important in determining and influencing organizational effectiveness.Therefore, the organizations should design their rules, policies and organizational structures that give space to the employee to work well and appreciate them on their tasks fulfillment and achievement.This will surely lead to organizational growth.